Economics, sustainability, and circularity: relevance for alternative economic models - Kumar, Shalander (International Crops Research Institute for the Semi-Arid Tropics, 2025)
Despite significant agricultural production growth, India's agri-food systems face critical sustainability challenges requiring alternative economic models. The current welfare-focused approach shows significant limitations, with widespread child stunting and protein deficiency among farm households despite operating the world's largest public distribution system. Agricultural household incomes remain inadequate for basic needs, while large parts of India face severe water stress and increasing climate risks threaten food security. This study examines the transition toward circular economy principles in agriculture as a pathway for sustainable development. Key challenges include resource degradation, high yield variability across districts, and the environmental burden of linear production systems. The circular economy approach integrates regenerative agriculture, organic recycling, bio-energy production, and monetization of ecosystem services. Evidence from implementations shows 20-30% reduction in post-harvest losses, 15-25% income increases, and improved resource efficiency. Critical pathways forward include developing regenerative agriculture suitability maps, strengthening local food systems, creating price incentives through green certification, and establishing measurement and verification systems for carbon trading.